Interaction Between a Non-Nodulating and an Ineffective Mutant of Rhizobium trifolli Resulting in Effective (Nitrogen-Fixing) Nodulation - Rolfe, B. G. (1980)
A noninvasive (non-nodulating) mutant of Rhizobium trifolii when mixed with an ineffective (non-nitrogen-fixing) mutant gives rise to effective (nitrogen-fixing) nodules.